Eksplorasi Bahasa Daerah Dalam Pembelajaran Bahasa Indonesia Untuk Memperkaya Kosa Kata - Abdul Latif Anshory; Ali Manshur (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This study examines the exploration of regional languages ​​in Indonesian language learning at SMP Plus Darussalam with the aim of enriching students' vocabulary and preserving local culture. This study examines the exploration of regional languages ​​in Indonesian language learning to enrich students' vocabulary. Social facts show that regional languages ​​increase students' connectedness to local culture and strengthen cultural identity. The literature emphasizes the importance of integrating regional languages ​​into the curriculum to facilitate a better understanding of linguistic diversity. The argument focuses on the positive impact of using regional languages ​​in increasing students' motivation and participation in the learning process. This study uses a qualitative approach, data were collected through interviews, observations, and documentation from students and teachers. The results showed that the integration of regional languages ​​increased students' enthusiasm, made them more connected to the teaching materials, and expanded their vocabulary. Students found it easier to understand new vocabulary related to everyday life, while the use of regional languages ​​also provided a rich cultural context. However, this study identified challenges in implementation, including the lack of support for teaching materials and training for teachers. Therefore, the importance of education policy support to facilitate the use of regional languages ​​in the curriculum is very much needed. These findings confirm that teaching involving regional languages ​​not only improves students' linguistic abilities, but also builds deeper cultural awareness, creating a generation that is more appreciative of Indonesia's linguistic and cultural diversity.